Pain through Lyrics: An Analysis of Implicature and Maxim Violations in Two DAY6 Sad Songs - Fathirunnisa, Amalia (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
Music primarily conveys emotion, most notably sadness, through unique expressive techniques. However, the social context built through the song lyrics can influence how the words are interpreted, which sometimes contrasts with their actual meaning. This research examines the use of implicature and maxim violations in DAY6’s sad songs titled Congratulations (English Version) and Zombie (English Version), which construct emotional meanings, by applying the pragmatic theory of social context, implicature, and maxim violations to analyze the lyrics of the songs. This study aims to identify how implicature and maxim violations appear in two DAY6’s songs and analyze the role of pragmatic deviations in expressing emotions. To accomplish these objectives, this study adapts a qualitative descriptive approach to show how implicature and maxim violations are used to create emotionally rich messages shaped by social context through a close reading of the lyrics. This research reveals that expressing feelings implicitly or indirectly evokes emotional resonance by stimulating listeners’ interpretation. Moreover, it also shows how language functions in song, specifically in conveying complex feelings without having to explicitly mention them. In addition, this study suggests that the Cooperative Principle can be adapted to various forms of communication and still remain effective in conveying the intended meaning.